Multisystem Synthesis of Radar Sounding Observations of the Amundsen Sea Sector From the 2004–2005 Field Season. Issue 10 (22nd October 2021) - Chu, Winnie; Hilger, Andrew M.; Culberg, Riley; Schroeder, Dustin M.; Jordan, Thomas M.; Seroussi, Helene; Young, Duncan A.; Blankenship, Donald D.; Vaughan, David G.
Abstract: The Amundsen Sea Embayment of the West Antarctic Ice Sheet contains Thwaites and Pine Island Glaciers, two of the most rapidly changing glaciers in Antarctica. To date, Pine Island and Thwaites Glaciers have only been observed by independent airborne radar sounding surveys, but a combined cross‐basin analysis that investigates the basal conditions across the Pine Island‐Thwaites Glaciers boundary has not been performed. Here, we combine two radar surveys and correct for their differences in system parameters to produce unified englacial attenuation and basal relative reflectivity maps spanning both Pine Island and Thwaites Glaciers. Relative reflectivities range from −24.8 to +37.4 dB with the highest values beneath fast‐flowing ice at the ice sheet margin. By comparing our reflectivity results with previously derived radar specularity and trailing bed echoes at Thwaites Glacier, we find a highly diverse subglacial landscape and hydrologic conditions that evolve along‐flow. Together, these findings highlight the potential for joint airborne radar analysis with ground‐based seismic and geomorphological observations to understand variations in the bed properties and cross‐catchment interactions of ice streams and outlet glaciers. Plain Language Summary: Pine Island Glacier (PIG) and Thwaites Glacier (TG) are the fastest‐changing outlet glaciers in West Antarctica. To understand how these glaciers move and evolve in the future, we need to understand processes that occur at the ice‐bed interface that control glacial motion. Here, we investigate the basal conditions of PIG and TG using radar sounding observations from two independent airborne surveys. By estimating the brightness and shape of radar power returns from the ice bed, we characterize the distribution of subglacial meltwater and how the subglacial landscape evolves along with ice flow. We also extend our radar interpretations using existing ground‐based seismic and geomorphology observations. These results show that PIG has a greater area of wet bed that extends far inland into the head of its ice tributaries. Meanwhile, TG has a patchier wet and locally frozen bed. Along the boundary of the two glaciers, we find that the presence of deformable sediments or subglacial meltwater, in addition to topography, also plays a role in explaining the present‐day configuration of ice flow. Future studies of ice sheet basal processes should more frequently combine airborne radar and ground‐based seismic and geomorphological observations to provide a unified interpretation. Key Points: We analyze two simultaneous 2004/2005 airborne radar surveys of Pine Island and Thwaites Glaciers conducted using different sounders We produce catchment‐wide englacial attenuation and basal reflectivity maps for Pine Island and Thwaites Glaciers Radar analysis reveals a critical frozen basal patch that currently separates the two neighboring glaciers